2021
DOI: 10.1017/s0007114521000635
|View full text |Cite
|
Sign up to set email alerts
|

No differences in muscle protein synthesis rates following ingestion of wheat protein, milk protein, and their protein blend in healthy, young males

Abstract: Plant-derived proteins have been suggested to have less anabolic properties when compared with animal-derived proteins. Whether blends of plant- and animal-derived proteins can compensate for their lesser anabolic potential has not been assessed. This study compares post-prandial muscle protein synthesis rates following the ingestion of milk protein with wheat protein or a blend of wheat plus milk protein in healthy, young males. In a randomized, double blind, parallel-group design, 36 males (23±3 y) received … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
73
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 48 publications
(81 citation statements)
references
References 41 publications
8
73
0
Order By: Relevance
“…Perhaps surprisingly, our findings indicate that the strength of evidence supporting the leucine trigger hypothesis is greater in older vs. young adults. In this regard, only three study arms in young adults provide evidence supporting the leucine trigger hypothesis ( 15 , 33 , 44 ), while seven studies refute the hypothesis ( 19 , 32 , 42 , 43 , 45 47 ). In contrast, the preponderance of evidence in older adults supports the leucine trigger hypothesis, with 13 studies reporting a greater post-prandial leucinemia following protein ingestion to correspond with an increased stimulation of MPS, and only seven studies reported a disconnect between the blood leucine concentration profile and post-prandial rates of MPS.…”
Section: Discussionmentioning
confidence: 92%
“…Perhaps surprisingly, our findings indicate that the strength of evidence supporting the leucine trigger hypothesis is greater in older vs. young adults. In this regard, only three study arms in young adults provide evidence supporting the leucine trigger hypothesis ( 15 , 33 , 44 ), while seven studies refute the hypothesis ( 19 , 32 , 42 , 43 , 45 47 ). In contrast, the preponderance of evidence in older adults supports the leucine trigger hypothesis, with 13 studies reporting a greater post-prandial leucinemia following protein ingestion to correspond with an increased stimulation of MPS, and only seven studies reported a disconnect between the blood leucine concentration profile and post-prandial rates of MPS.…”
Section: Discussionmentioning
confidence: 92%
“…Only a handful of studies have directly compared postprandial muscle protein synthesis rates following ingestion of plant-versus animal-derived proteins [13,14,16,[36][37][38]. Ingestion of soy protein has been shown to be less effective in stimulating post-prandial muscle protein synthesis rates when compared with the ingestion of an equivalent amount of whey protein in both young and older adults at rest and during recovery from exercise [13,14,36], but more effective than casein protein [13].…”
Section: Amino Acid Composition Of Proteinmentioning
confidence: 99%
“…Not surprisingly, this also raises questions regarding the impact of the (lower) quality of plant-based proteins on muscle conditioning during recovery from exercise. There are only a handful studies that have compared post-exercise muscle protein synthetic responses following the ingestion of plant-versus animalderived proteins [13,14,16,[36][37][38]. In these studies, the main plant-derived protein that has been applied is soy protein.…”
Section: Plant-based Proteins In Sports Nutritionmentioning
confidence: 99%
See 2 more Smart Citations